ZIZEK: AMBIVALENCE AND OSCILLATION - Parker, Ian (PINS-Psychology in Society, 2026)
Writing by the Slovenian philosopher and psychoanalytic researcher Slavoj Z1zek has assumed immense importance in cultural and political theory in the last ten years, and his combination of ideas from Hegelian phenomenology, Lacanian psychoanalysis and Marxist politics has provided new ways of thinking about the relationship between ideology, subjectivity and revolutionary change. This article reviews the way that Zizek juggles different theoretical elements in his work, and serves as a brief introduction to a body of writing that is confusing and contradictory. Two points are highlighted. First, that the theoretical elements (Hegel, Lacan and Marx) are used by Zizek in a quite idiosyncratic manner, and we need to notice how he moulds them for his own purposes. Second, that there is an intimate connection between the "political" project that Zizek is elaborating and radical (perhaps even more radical) artistic practices in Slovenia.